Home on a care order: who the children are and what the care order is for. Issue 2 (7th June 2016) - Fargas‐Malet, Montserrat; McSherry, Dominic; Pinkerton, John; Kelly, Greg
Abstract: Compared to children in other placements, there is much less known about the characteristics and needs of children in the UK who are returned to their birth parents with a care order still in place. That is in spite of evidence to suggest they face more difficulties than young people in other placements. Based on a 2009 census of looked after children in Northern Ireland, just under 10% ( n = 193) were found to be living at home under a care order. Case file reviews were conducted for a quarter of these young people ( n = 47) to generate descriptive statistics showing a very diverse population. That was followed by semi‐structured interviews with members of eight families (ten children and eight birth parent/s), providing transcripts for thematic analysis. Nearly half of the young people whose case files were reviewed had experienced at least one home placement breakdown, but nearly two thirds had a stable last home placement. Care orders appeared to serve two functions: to give legal authority to social services for the monitoring of placements, and to facilitate family access to family support services. Replacing some care orders with supervision orders might better align legal status and actual function.